Application Of arabic Language Rules To Students Of SMA Al Baladul Amin Kandangan And MA Ummul Qura Amuntai - Imam Dhia Ul Islam; Ridha Fadillah (Jurnal Al-Maqoyis, 2021)
The research is intended to explore the application of Arabic language rules to students of SMA Al Baladul Amin Kandangan and MA Ummul Qura Amuntai. This study departs from the researcher's initial observation that many of the students are passive in Arabic. Some of them are active but the grammar is not good and some students have a lot of vocabulary but they cannot use them in speaking. In addition, many students find it difficult to learn Arabic, especially in memorizing vocabulary and learning grammar as well. The results of this study indicate that 1) Arabic vocabulary used by students is illustrated by; a) The suitability of the given vocabulary. The Arabic teacher of SMA al-Baladul Amin has provided vocabulary to his students by adjusting to the subject being studied and the daily needs of students in communicating among students. The Arabic teacher of MA Ummul Qura has given vocabulary to his students by adjusting to the subject being studied. b) The ability of students to memorize the given vocabulary. High school students al-Baladul Amin did not find it difficult to memorize Arabic vocabulary. Meanwhile, MA Ummul Qura students still find it difficult to memorize Arabic vocabulary. c) Students' ability to practice vocabulary. Al-Baladul Amin high school students are easy to practice Arabic vocabulary. Meanwhile, MA Ummul Qura students still have difficulty in practicing Arabic vocabulary. 2) Arabic grammar used by students is illustrated from; a) Procedures for teaching teachers to students about grammar. The Arabic teacher of SMA al-Baladul Amin teaches his students by giving an explanation first and then immediately putting it into practice. The Arabic teacher of MA Ummul Qura teaches his students by lecturing or explaining the grammar in Arabic and occasionally asking some students. b) Students' ability to understand grammar. Al-Baladul Amin High School students easily understand Arabic grammar. As for the MA Ummul Qura students, it is difficult to understand Arabic grammar. c) Students' ability to practice grammar. Application, Rules in Arabic, and Arabic.